2007
DOI: 10.1175/jcli4049.1
|View full text |Cite
|
Sign up to set email alerts
|

The Global Trend in Sea Surface Temperature from 20 Years of Advanced Very High Resolution Radiometer Data

Abstract: The trend in sea surface temperature has been determined from 20 yr of Advanced Very High Resolution Radiometer Pathfinder data (version 5). The data span the period from January 1985 to December 2004, inclusive. The linear trends were calculated to be 0.18°Ϯ 0.04°and 0.17°Ϯ 0.05°C decade Ϫ1 from daytime and nighttime data, respectively. However, the measured trends were found to be somewhat smaller if version 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 14 publications
5
46
0
Order By: Relevance
“…Although this process can be considered as one of the key linkages between the North Atlantic and South Atlantic waters, the differences in trends suggest that different processes may have an influence. Chollett et al, (2012) decade, which lies within the range of 0.2 and 0.6 ºC/decade found by Strong et al (2008) based on the period 1985 to 2006, and close to the estimation by Good et al (2007), who reported 0.3 ºC/decade for the period 1985 to 2003. We found values between 0.05 and 0.27 ºC/decade for the boxes with positive trend within the Atlantic side of our study period.…”
Section: Atlantic Regionsupporting
confidence: 90%
“…Although this process can be considered as one of the key linkages between the North Atlantic and South Atlantic waters, the differences in trends suggest that different processes may have an influence. Chollett et al, (2012) decade, which lies within the range of 0.2 and 0.6 ºC/decade found by Strong et al (2008) based on the period 1985 to 2006, and close to the estimation by Good et al (2007), who reported 0.3 ºC/decade for the period 1985 to 2003. We found values between 0.05 and 0.27 ºC/decade for the boxes with positive trend within the Atlantic side of our study period.…”
Section: Atlantic Regionsupporting
confidence: 90%
“…For example, the NOAA Pathfinder dataset (http://www.nodc.noaa.gov/sog/pathfinder4km) [189] has permitted an examination of recent global and regional trends in SST anomalies [190,191] and thermal stress [192,193].…”
Section: Sea Surface Temperature (Sst)mentioning
confidence: 99%
“…environments are even more scarce (Hudson et al 1991), but starting in the 1990s, the deployment of fixed sensors (Ogden et al 1994) and accurate, yet inexpensive, temperature loggers has lessened this data gap. Also, SST has been monitored remotely from space since the 1980s with satellite-mounted radiometers that produce infrared imagery (Good et al 2007).…”
Section: Datasets Measuring Subsurface Temperatures In Coral Reefmentioning
confidence: 99%